Effects of institutional environment and technology development on payment choice - Callado-Muñoz, Francisco J.; Hromcová, Jana; Utrero-González, Natalia (Technological and Economic Development of Economy, 2018)
The purpose of this paper is to analyze the combination of institutional factors and technology advances as determinants for the choice of payment instruments. The theoretical set up suggests that countries that enter into a new institutional environment adopt the attitudes of the accepting group towards the payment choices as a consequence of institutional pressure and technology development. We apply the results of the model to the European Union enlargement process of 2004. Our findings confirm the relevance of both institutional environment and technology development in retail payment choice decisions particular to Central and Eastern European Countries.First published online 2 November 2015